Randomised controlled trial of short bursts of a potent topical corticosteroid versus prolonged use of a mild preparation for children with mild or moderate atopic eczema - Thomas, K.S.; Armstrong, S.J.; Avery, Anthony; Li Wan Po, A.; O'Neill, C.; Young, S.; Williams, H.C. (BMJ Publishing Group, 2002)
Objective To determine whether a three day burst of a potent corticosteroid is more effective than a mild preparation used for seven days in children with mild or moderate atopic eczema. Design Randomised, double blind, parallel group study of 18 weeks' duration. Setting 13 general practices and a teaching hospital in the Nottingham area. Participants 174 children with mild or moderate atopic eczema recruited from general practices and 33 from a hospital outpatient clinic. Interventions 0.1% betamethasone valerate applied for three days followed by the base ointment for four days versus 1% hydrocortisone applied for seven days. Main outcome measures Primary outcomes were total number of scratchfree days and number of relapses. Secondary outcomes were median duration of relapses, number of undisturbed nights, disease severity (six area, six sign atopic dermatitis severity scale), scores on two quality of life measures (children's life quality index and dermatitis family impact questionnaire), and number of patients in whom treatment failed in each arm. Results No differences were found between the two groups. This was consistent for all outcomes. The median number of scratchfree days was 118.0 for the mild group and 117.5 for the potent group (difference 0.5, 95% confidence interval - 2.0 to 4.0, P = 0.53). The median number of relapses for both groups was 1.0. Both groups showed clinically important improvements in disease severity and quality of life compared with baseline. Conclusion A short burst of a potent topical corticosteroid is just as effective as prolonged use of a milder preparation for controlling mild or moderate atopic eczema in children.